Hemostasis of the radial artery after coronary angiography: a scoping review. (2nd July 2022) - Teixeira Rodrigues, D; Teixeira, C; Parola, V; Marques, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Nowadays, most interventional cardiology procedures are made via radial artery. There is significant variability of haemostasis methods, devices, and protocols. All of them try to avoid radial artery occlusion while maintaining patent haemostasis. Summarizing the available evidence about haemostasis of the radial artery after coronary angiography will allow us to challenge our current practice. Purpose: The focus of this scoping review is to map the literature on haemostasis of the radial artery after coronary angiography. To date, no previous reviews addressing this purpose have been found. Methods: This review follows the Joanna Briggs Institute methodology for scoping reviews. Two reviewers will independently perform the study selection regarding their eligibility. Data extraction will be accomplished using a researcher's developed tool to address the objectives and reviews questions. Any disagreements arisen between the reviewers will be resolved by discussion or consulting a third reviewer. Data synthesis will be presented in tabular form and a narrative summary that align with the review's objective. Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension to scoping reviews guidelines will be used to report the results. A set of relevant electronic databases and grey literature will be searched. Results: Twenty-four studies were included, of various types: randomized clinical trials, case-reports, case series, narrative reviews. Three methods were described: compression devices, compression band and haemostatic patch. Sometimes more than one method is used, and there are various protocols that vary according to the institutional practice. Conclusion: There are multiple radial artery haemostasis methods and protocols currently in use after a coronary angiography with no method overwhelmingly predominant. Few were associated with clearly defined haemostasis protocols, even though these protocols exist, often associated with compression devices. The institutional practice plays a decisive role on the use and modification of these protocols, with no clear evidence to support it. Such variability in protocols might have a detrimental effect in having a standardized one that can be used across various institutions/countries, facilitating broader multicentric studies.